DISIPLIN KERJA, MOTIVASI DAN JOB ENGAGEMENT PENGARUHNYA TERHADAP KINERJA KARYAWAN BNS (BATU NIGHT SPECTACULER) KOTA BATU - Didik Suliono; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT This study aims to find out work, motivation, and job involvement on employee performance. The sample in this study invited 60 people who were employees of BNS in Batu city.The method that is descriptive data analysis is by using validity, reliability, normality, multiple linear regression analysis, multicolonierity test, t hypothesis test, and hypothesis testing f.The results of this study indicate that each of the variables of work discipline, motivation and work involvement are equally influential on performance, as well as work variables, motivation and work involvement as well as the influence of the performance of the BNS company in Batu city. Keywords: work discipline, motivation, work involvement, employee performance